Unraveling the fine-tuned lemon coloration of a pierid butterfly Catopsilia pomona. (28th September 2017) - Mishra, Monalisa; Choudhury, Ashutosh; Achary, P Sagar; Sahoo, Harekrushna
Abstract : The Catopsilia pomona wing is divided into yellowish green, greenish white and black color. The greenish white occupies the major region. The dorsal region of this part has a typical arrangement within the scales with hairy scales in the margin. The ventral portion scale has ladder like arrangement (Fig. 4 ). Abstract: Butterflies wings possess different types of scales to perform diverse functions. Each scale has many nano and microstructures, which interferes with light, resulting in unique coloration for each butterfly. Besides coloration, the arrangement of scales further helps in giving better survivability. Thus, analysis of wing pattern provides an overall idea about adaptation and activity of the animal. The current study deciphers the structure and composition of a wing of a pierid butterfly Catopsilia pomona, which remains active at 42°C at which temperature all other butterflies face a tougher task for existence. In order to know the relation between survivability and adaptation in the wing, we have investigated the structural and physical composition of the wing of C. pomona under optical spectroscopy (absorption, reflectance and transmittance) along with microscopy techniques (optical and scanning electron microscopy), which are not described in earlier studies. The current findings reveal unique structural arrangement within scales to provide the best fit to the animal in variable temperature.